Variable phenology but consistent loss of ice cover on 1213 Minnesota lakes - Jake R. Walsh; Christopher I. Rounds; Kelsey Vitense; Holly K. Masui; Kenneth A. Blumenfeld; Peter J. Boulay; Shyam M. Thomas; Andrew E. Honsey; Naomi S. Blinick; Claire L. Rude; Jonah A. Bacon; Ashley A. LaRoque; et al. (Limnology and Oceanography Letters, 2025)
Abstract Lake ice cover is declining globally with important implications for lake ecosystems. Ice loss studies often rely on small numbers of lakes with long‐term data. We analyzed variation and trends in ice cover phenology from 1213 lakes over 74 yr (1949–2022) in Minnesota (USA), during which ice cover duration declined at a rate of 2 d per decade (14 d total) and became more variable. Despite variation in phenology, just 10–20% of lakes differed from statewide phenological trends. Accounting for synchronous annual variation and estimating trends over long time periods (e.g., > 40 yr) were critical for obtaining robust estimates of ice loss. The constant rates estimated here were consistent with recent global estimates (1.7–1.9 d per decade) and suggest that, even if present, accelerating rates of ice loss could be difficult to detect in the midst of shorter‐term periods of warming and increasing variability.